2006
DOI: 10.1542/peds.2005-2126
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Flat Foot in Preschool-Aged Children

Abstract: This study is the first to use a three-dimensional laser surface scanner to measure the rearfoot valgus in preschool-aged children. The data demonstrate that the prevalence of flat foot is influenced by 3 factors: age, gender, and weight. In overweight children and in boys, a highly significant prevalence of flat foot was observed; in addition, a retarded development of the medial arch in the boys was discovered. At the time of the study, > 90% of the treatments were unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
337
8
29

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(428 citation statements)
references
References 16 publications
28
337
8
29
Order By: Relevance
“…*= Correlation is significant at the 0.05 level (2-tailed). Pfeiffer et al (2006) showed that 3 variables had a significant relationship to the prevalence of flexible flat foot: age, sex, and weight but in these study no significant difference between female and male. Morrison et al (2007) indicated that differences in foot length, forefoot width, and navicular height were presented in children of excessive body mass compared with those of normal body mass.…”
Section: Discussioncontrasting
confidence: 54%
“…*= Correlation is significant at the 0.05 level (2-tailed). Pfeiffer et al (2006) showed that 3 variables had a significant relationship to the prevalence of flexible flat foot: age, sex, and weight but in these study no significant difference between female and male. Morrison et al (2007) indicated that differences in foot length, forefoot width, and navicular height were presented in children of excessive body mass compared with those of normal body mass.…”
Section: Discussioncontrasting
confidence: 54%
“…Many maintain that most asymptomatic flat feet do not need any treatment 7,8) ; however, there may are many possible results of neglected flat feet 9) . Staheli 10) mentioned that flat feet were normal or physiological in infants, children, and some adults.…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences in prevalence of flat foot is also found in overweight, obese, and normal-weight children and boys showed a significantly greater tendency for flat foot than girls [6]. It seems that different variables such as age, weight and gender may influence the prevalence rates when the subject's feet are examined in static, mainly standing positions.…”
Section: Discussionmentioning
confidence: 95%
“…This classification could be described by OPS measurement methods. Pfeiffer et al [6], reported a prevalence of 44% in a group of 835 (411 girls and 424 boys) children of 3 to 6 years old (52% in boys and 36% in girls). They used a three-dimensional laser surface scanner with the subjects in a standing position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation